Implementation of an electromagnetic system for controlling resistance and speed in indoor cycling - Moreno-González, Jairo A.; Alarcón-Aldana, Andrea Catherine; Callejas-Cuervo, Mauro (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Advances in knowledge and technology in various fields of human life and, particularly, in sports have resulted in innovative systems for professional sportsmen training. Here, we designed an electromagnetic system for practicing indoor cycling; this system can precisely simulate on the track the ascents and descents that allow the users to feel like they are training outdoors. Furthermore, this system connects to a web application that allows access from any mobile device to predefine the training routines and thus improve the user experience.